Gender-Differences in aortic dissection - Yu-Jang Su; Che-Hung Liu; Yu-Hang Yeh (Journal of Acute Disease, 2014)
Objectives: Aortic dissection is a truly emergency in daily practice, and for gender factor, we want to compare the epidemiology, biomarkers, symptoms and outcome. Methods: A retrospective review six-year AD cases in a northern Taiwan medical center from January, 1, 2005 to December, 31, 2010. by gathering data of 134 AD patients including gender, age, episodes of time, season, vital signs, symptoms (chest pain, chest tightness (CP/CT), abdominal pain, neurological symptoms), Stanford classifications, and outcome. Comparisons are made by gender of AD groups. 85 cases with complete data are strictly enrolled into our study. We used student t test and one way ANOVA for statistical analyses, and significance was set at a P value less than 0.05 (2-tailed). Results: There are 64 male and 21 female enrolled into our study with the mean ± standard deviation (SD) of age is (64.1±14.0) years old. In AD patients with female gender are older than male AD patients (71.5 vs. 61.6 years old, P value<0.01). In symptoms of presentation, female AD patients have more neurologic symptoms than male AD patients (38.1% vs. 12.5%, P <0.01). Female AD patients have longer hospital stay and higher mortality rate than male AD patients (16.8 vs. 13.4 d; 38.1% vs. 18.8%, P =0.39; P =0.07). Conclusion: Female AD patients are ten-year older in age than male, and have more common neurologic symptoms in presentations, and female AD patient have 2-fold mortality rate than male AD patients.